Legality of General Physicians in Ultrasound Examination in Daily Practice - Sudomo Colombus Situmorang; Beni Satria; Redyanto Sidi (Berpusi Publishing, 2023)
Ultrasound is something technology that can describe in body somebody. If There is identified complications, then can done more handling fast. Basically doctor In general, you can perform an ultrasound on the patient. But since appearance Regulation Minister Health Number 24 of 2020 concerning Service Radiology Clinic, doctor specialist or doctor general own authority very limited to facility radiology including ultrasound. Based on the problems mentioned above, researchers see exists problem that is where general practitioners currently have very limited authority to provide ultrasound health services to patients. In practice, from the research results it can be seen that based on Regulations Minister Health Number 75 202 3 concerning technical instructions for the use of ultrasound equipment for general practitioners in primary care. It is currently legal for general practitioners to perform ultrasound provided that the general practitioner Already follow education And training standardized for basic ultrasound limited because of someone doctor said has competent in do basic ultrasound examination limited when has follow education And formal ultrasound training ( during education doctor ) or through recognized workshops by Ministry Health and POGI ( USG Working Group ) and Then obtain certificate.